Influence of Online Customer Reviews and Online Customer Ratings on Purchase Intention with Perceived Risk as an Intervening Variable on Potential Tokopedia E-Commerce Users in Padang City - Arif Rahman Azwar; Yunia Wardi (SAFE-Network, 2026)
This study aims to analyze the influence of online customer reviews and online customer ratings on purchase intention, with perceived risk serving as an intervening variable among potential tokopedia e-commerce users in padang city. In Particular, this study focuses on analyzing the influence of online customer reviews and online customer ratings on purchase intention, with perceived risk serving as an intervening variable, among prospective Tokopedia e-commerce users in Padang City. This study involved 272 prospective Tokopedia e-commerce users in Padang City, selected through purposive sampling based on specific criteria, using SmartPLS Version 3.0 for data analysis to test the relationships within the SEM model. The results indicate that online customer reviews and online customer ratings have a direct influence on purchase intention, with perceived risk serving as an intervening variable. The findings confirm that all hypotheses are supported. Online customer reviews and online customer ratings were found to have a positive and significant influence on purchase intention, both directly and through perceived risk as an intervening variable. Additionally, perceived risk alone has a significant impact on determining consumer purchase intention. These findings indicate that online customer reviews and ratings play a crucial role in enhancing consumer purchase intention and are capable of minimizing perceived risk, thereby serving as an effective strategy for e-commerce platforms to build user trust and loyalty.